TINJAUAN PERUBAHAN LAYANAN EKOSISTEM AKIBAT PERLUASAN PERTANIAN DAN PERTAMBANGAN DI DAS TROPIS - La Ode, Rustam; Mulya, Setyardi Pratika Mulya (BIOMA : JURNAL BIOLOGI MAKASSAR, 2026)
The expansion of agricultural and mining areas in tropical watersheds (DAS) has resulted in changes in ecosystem services (ES), which have been under pressure for decades. This study uses a systematic literature review (SLR) by synthesizing articles published in the Scopus database between 2009 and 2025 using the PRISMA Flow Diagram 2020 framework. The keyword combinations used include "Ecosystem Service", "Watershed OR River Basin", "Land Use AND Agricultural OR Plantation OR Oil Palm OR Mining", and "Tropical". Bibliometric analysis using R-studio and VOSviewer was conducted to examine the distribution of articles and the interconnectedness of ecosystem services. The synthesis results indicate that agricultural expansion is a change driver with broader impacts, fundamentally altering the landscape and causing long-term cumulative impacts. Meanwhile, mining tends to be a pressure driver with very sharp and toxic local impacts. Declines occur in regulating services, especially for sediment retention, water filtration, and carbon storage. Service providers such as agricultural and mineral production have increased in the short term, creating significant trade-offs that have the potential to damage tropical watersheds. The research review results indicate the dominance of the InVEST and SWAT models in ES assessments, but there is still a lack of continuous field validation. Other information related to the forest cover threshold of around 50-60% is a critical factor in maintaining hydrological and biogeochemical regulation in tropical watersheds. This review also emphasizes the need to protect and limit forest clearing for sustainable and environmentally friendly land management practices and emphasizes that watershed management needs to shift from a productivity-focused approach to ecosystem service-based management. Sustainable management responses that need to be implemented to improve ecosystem services through reforestation, implementation of conservation measures, and economic compensation for improved ecosystem services in tropical watersheds. Keywords: Keywords: Ecosystem Services, Agriculture, Mining, Tropical Watersheds